BUILD CUSTOMIZED APPS WITH AMAZON HONEYCODE quickly create interactive web and mobile apps for your teams without programming. - LOYA, ANIRUDDHA (PACKT PUBLISHING LIMITED, 2022)
A non-developer's guide to harnessing the power of Amazon Honeycode apps to manage projects, customers, operations, approvals, resources, and teams Key Features A practical guide to Amazon Web Services (AWS) no-code app development for meeting specific needs of customers Create apps quickly without paying for costly developers using Honeycode's in-built templates and functions Learn how to use stable AWS services to supplement Honeycode's present limits Book Description Amazon Honeycode enables you to build fully managed, customizable, and scalable mobile and web applications for personal or professional use with little to no code. With this practical guide to Amazon Honeycode, you'll be able to bring your app ideas to life, improving your and your team's/organization's productivity. You'll begin by creating your very first app from the get-go and use it as a means to explore the Honeycode development environment and concepts. Next, you'll learn how to set up and organize the data to build and bind an app on Honeycode as well as deconstruct different templates to understand the common structures and patterns that can be used. Finally, you'll build a few apps from scratch and discover how to apply the concepts you've learned. By the end of this app development book, you'll have gained the knowledge you need to be able to build and deploy your own mobile and web applications. You'll also be able to invite and share your app with people you want to collaborate with. What you will learn Build mobile and web applications with simple drag-drops and customizations Deploy and share apps and collaborate in real-time with your team Understand how to create automated processes in apps Create a customized view for each app user or a group of users Import existing data from a CSV and build an app on top of it Create connectors to external data sources Build applications using Honeycode either from scratch or by modifying an existing template Explore Honeycode templates and understand what use cases are available out-of-the-box with these templates Who this book is for Like the platform, this book is meant for everyone - professional and novice developers alike - who want to build and deploy apps for their personal or professional use as an individual or as a team. However, for professional developers, it is important to note that the book will not focus on advanced use cases with features like using public APIs and 3P integrations. No programming knowledge or experience is needed to start creating basic apps. However, working knowledge of Microsoft Excel or similar spreadsheet tools and a general understanding of logical statements will be helpful to get the most out of this book.